THE IMPACT OF CHANGES IN TAX LEGISLATION ON THE ECONOMIC STABILITY OF UKRAINE - Bukanov, Hryhorii; Kuzmenko, Olena; Volokhov, Oleksii (Social Development: Economic and Legal Issues, 2025)
The article investigates the impact of changes in Ukraine’s tax legislation on the country’s economic stability, with a particular focus on the conditions of martial law and post-war recovery. The analysis draws on scholarly works by Ukrainian researchers, legislative and regulatory acts, statistical data from the State Tax Service of Ukraine, and analytical reports from international organizations. The study explores the theoretical foundations of the relationship between tax policy and economic stability, highlighting its influence through fiscal, regulatory, distributive, and stabilization channels. It demonstrates that tax policy is pivotal in shaping budget revenues, fostering entrepreneurial activity, and creating a favorable investment climate. The article examines key changes in Ukraine’s tax legislation, including the expansion of the simplified taxation system, reduced VAT rates for specific goods, and deferred tax obligations during the war. While these measures supported businesses, they also led to reduced budget revenues and increased opportunities for tax optimization, posing risks to financial stability. The study identifies major challenges: legislative instability, violations of the stability principle, uneven tax burden, low tax culture, high levels of tax-related corruption, and rising tax debt. Special attention is given to the inefficiency of the simplified taxation system, which has become a mechanism for tax evasion. Recommendations for improving tax legislation include ensuring stability, aligning with EU standards, optimizing the tax burden, digitizing tax administration, ensuring equal taxation conditions, reforming the simplified system, and fostering tax culture. The article emphasizes that the effectiveness of tax legislation hinges on adherence to the rule of law and clarity of norms, which are crucial for Ukraine’s economic revival. The research is relevant for scholars, policymakers, and practitioners developing tax policy strategies amid crisis and European integration.